New Insight of microRNAs & short interfering RNA in Treatment of COVID-19; a Narrative Review - Salahshoor, Mohammad Ali; Mahjub, Reza (Archives of Men's Health, 2022)
Since 31 December 2019, the coronavirus disease 2019 (COVID-19) resulted in a state of hyperinflammation syndrome and multiorgan failure. In areas with pandemic outbreaks, despite several emerging vaccines, supportive treatments to mitigate fatality rates were required. Growing evidence suggests that several small RNAs such as microRNAs (miRNAs) and short interfering RNA (siRNA) could be candidates for the treatment of COVID-19 by inhibiting the expression of crucial virus genes. small RNAs by binding to the 3′-untranslated region (UTR) or 5′-UTR of viral RNA play an important role in COVID-19-host interplay and viral replication. In this review, the authors sought to specify the efficacy and safety of miRNAs and siRNA expressions of patients with COVID-19, which has an axial role in the pathogenesis of human diseases.